Clinical outcomes and immune responses to SARS‐CoV‐2 vaccination in severe aplastic anaemia. (21st September 2022) - Rajput, Roma V.; Ma, Xiaoyang; Boswell, Kristin L.; Gaudinski, Martin; Gordon, Ingelise; Novik, Laura; Groarke, Emma M.; Lotter, Jennifer; Superata, Jeanine; Rios, Olga J.; Darden, Ivana; Lin, Bob C.; et al.
Summary: Patients with severe aplastic anaemia (SAA) are often not vaccinated against viruses due to concerns of ineffective protective antibody response and potential for pathogenic global immune system activation, leading to relapse. We evaluated the impact of COVID‐19 vaccination on haematological indices and disease status and characterized the humoural and cellular responses to vaccination in 50 SAA patients, who were previously treated with immunosuppressive therapy (IST). There was no significant difference in haemoglobin ( p  = 0.52), platelet count ( p  = 0.67), absolute lymphocyte ( p  = 0.42) and neutrophil ( p  = 0.98) counts prior to and after completion of vaccination series. Relapse after vaccination, defined as a progressive decline in counts requiring treatment, occurred in three patients (6%). Humoural response was detectable in 90% (28/31) of cases by reduction in an in‐vitro Angiotensin II Converting Enzyme (ACE2) binding and neutralization assay, even in patients receiving ciclosporin (10/11, 90.1%). Comparison of spike‐specific T‐cell responses in 27 SAA patients and 10 control subjects revealed qualitatively similar CD4 + Th1‐dominant responses to vaccination. There was no difference in CD4 + ( p  = 0.77) or CD8 + ( p  = 0.74) T‐cell responses between patients on or off ciclosporin therapy at the time of vaccination. Our data highlight appropriate humoural and cellular responses in SAA previously treated with IST and true relapse after vaccination is rare.